A compliant microstructured thermal interface material for dry and pluggable interfaces. (March 2019) - Cui, Jin; Wang, Jicheng; Weibel, Justin A.; Pan, Liang
Highlights: A thermal interface material for dry and nonflat interfaces under a low pressure. A scalable fabrication method and electroless metal plating. Thermal resistance outperforms direct metal-to-metal contact. Compression cycling tests confirm the mechanical durability of the structure. Insertion approach demonstrates use as an attachable thermal interface material. Abstract: Thermal interface materials (TIMs), such as thermal pastes and pads, can successfully enhance contact thermal conductance by filling the gaps caused by the surface nonflatness and roughness. However, there is still an unaddressed demand for TIMs which can be applied to pluggable or reworkable interfaces in electronic systems, such as in opto-electronic transceiver modules. Reducing the contact thermal resistances at these interfaces has become increasingly important as device power density increases. These applications require dry contact interfaces that can offer the required thermal conductance under a low pressure and endure repeated mechanical compression and shear. We present a compliant metallized finned zig zag micro-spring array, as a low-cost dry TIM, that allows conformal interface contact at low pressures (∼10–100 s of kPa) by effectively accommodating surface nonflatness at a rate of a few µm per kPa. Experimental characterization of the mechanical compliance and thermal resistance confirm that this dry TIM can achieve conformal thermal contact between nonflat mating surfaces under low pressures. The total insertion thermal resistance of this dry TIM, even when mating to nonflat surfaces, is comparable to that of a polished and flat metal-to-metal contact. Mechanical compression and shear cycling tests are performed to assess the durability.